Mmwave synthetic aperture radar (SAR) imaging with denoising - Zhang, Di (Nanyang Technological University, 2021)
In this thesis, an imaging in-depth strategy base on millimeter-wave synthetic aperture radar scanning using FMCW with a center operating frequency of 77GHz has been presented. IWR1443 Boost, which is a mmWave sensor with an integrated antenna from Texas Instrument, has been utilized with a data capturing board DCA1000EVM. The cascaded boards are mounted on a cross-placed shelf with step motors which are controlled by MATLAB commands. The thesis explained elementarily the principle of mmWave imaging using the hardware equipment noted above, with specific discussion on the cause of noise and aliasing, and hereby argued for the inevitability of aliasing in imaging under certain circumstances, raising up the requirement for image denoising algorithms. This thesis includes research into the idea of virtual aperture, by introducing which, the synthetic aperture radar is now capable of capturing the image reconstruction data quicker and more precisely than before, with better resolution considerations. Image enhancement methods are also introduced, with properly designed image processing algorithms, the scanned images are more suitable for machine learning algorithms to train on distinguishing the objects. Discussions on the possible application scenarios and future improvements are also included.